2022
DOI: 10.1111/dme.14931
|View full text |Cite
|
Sign up to set email alerts
|

From clinic to community: A randomized controlled trial of a peer support model for adults with type 2 diabetes from specialty care settings in British Columbia

Abstract: Aims To examine the impact of a 12‐month peer‐led diabetes self‐management support intervention delivered via telephone amongst adults with type 2 diabetes (T2D) from specialty care settings in British Columbia (BC). Methods One‐hundred ninety‐six adults with T2D were randomly assigned to either a 12‐month Peer‐Led, Empowerment‐based, Approach, to Self‐management Efforts in Diabetes (PLEASED) intervention or a usual care condition. PLEASED involved weekly telephone contacts from a peer leader (PL) in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Peer Leader Supported Self-Care Intervention Although large numbers of patients with T2DM receive diabetes care in primary care settings, patients at the highest risk are often managed in subspecialty settings. Tang and colleagues conducted a peer-led intervention for adult T2DM patients presenting to endocrinology and diabetes education centers in British Columbia, Canada [32] and compared it to a usual care control group. Peer leaders completed 30 h of knowledge and skills training in T2DM self-management, providing emotional support, and linking patients to clinical resources.…”
Section: Peer Coaches and Peer Mentorsmentioning
confidence: 99%
“…Peer Leader Supported Self-Care Intervention Although large numbers of patients with T2DM receive diabetes care in primary care settings, patients at the highest risk are often managed in subspecialty settings. Tang and colleagues conducted a peer-led intervention for adult T2DM patients presenting to endocrinology and diabetes education centers in British Columbia, Canada [32] and compared it to a usual care control group. Peer leaders completed 30 h of knowledge and skills training in T2DM self-management, providing emotional support, and linking patients to clinical resources.…”
Section: Peer Coaches and Peer Mentorsmentioning
confidence: 99%
“…The goal of this study was to ‘perform an autopsy’ on a telephone‐based, peer support intervention targeting adults with type 2 diabetes (T2D) from speciality care settings 19 . Specifically, the objectives of this study were to explore participants' experience with and perspective of the intervention and determine what modifications could be made to improve future iterations.…”
Section: Introductionmentioning
confidence: 99%
“…12 The goal of this study was to 'perform an autopsy' on a telephone-based, peer support intervention targeting adults with type 2 diabetes (T2D) from speciality care settings. 19 Specifically, the objectives of this study were to explore participants' experience with and perspective of the intervention and determine what modifications could be made to improve future iterations. Although this study does not focus on participant experience as it relates to clinical outcomes, it should be noted that this randomized controlled trial (RCT) found no difference in A1c between the intervention (i.e.…”
Section: Introductionmentioning
confidence: 99%